The Bali agreement, at last: An assessment from the perspective of developing countries - Díaz-Bonilla, Eugenio; Laborde Debucquet, David (International Food Policy Research Institute, 2014)
This paper discusses the results of the Bali Ministerial Conference of December 2013 (sometimes called the “Bali Pack-age”), the problems encountered during 2014, and how were they solved in November 2014, as well as the potential implications for the post-Bali work program which remains critical to unlocking the Doha Round.